DINAMIKA POPULASI UDANG DOGOL (Penaeus indicus H.Milne. Edwards 1837) DI LAGUNA SEGARA ANAKAN CILACAP JAWA TENGAH - Suradi W. Saputra (Universitas Gadjah Mada, 2008)
The research of population dynamic of Penaeus indicus was held on Segara Anakan Lagoon, Cilacap Central Java. This research aimed to study of the growth, length of first capture (Lc), and mortality of Penaeus indicus. The research were carried out from July to December 2004 using survey method, and the samples were collected by sistematic sampling method. Data was analyzed using ELEFAN in FiSAT II software. The result show that the first capture of carapace length was 20.4 mm. Growth pattern of P. Indicus was negative allometric (b = 2.44). Maximum carapace length in sample was 33.5 mm and L∞ = 35.7 mm, and index of curve growth (K) = 1.26 per year and to = - 0.0438 year. Time of inflection growth rate point was 0.438 year, on carapace length 16 mm. Total mortality (Z) was 3.95/years, natural mortality was 2.6/years and fishing mortality was 1.35/years, hence mortality was dominated by natural mortality.